2010
DOI: 10.1007/s00018-010-0597-y
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and aging: increased resistance to apoptosis enhances the aging process

Abstract: Apoptosis is a vital component in the evolutionarily conserved host defense system. Apoptosis is the guardian of tissue integrity by removing unfit and injured cells without evoking inflammation. However, apoptosis seems to be a double-edged sword since during low-level chronic stress, such as in aging, increased resistance to apoptosis can lead to the survival of functionally deficient, post-mitotic cells with damaged housekeeping functions. Senescent cells are remarkably resistant to apoptosis, and several s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 111 publications
6
91
1
Order By: Relevance
“…The mechanism by which NF-kB signaling is activated with age also remains largely unexplored, but our data indicate that the nuclear envelope abnormalities occurring in both normal and premature aging (Scaffidi and Misteli 2006) may contribute, at least in part, to the activation of this inflammatory pathway. The primary function of NF-kB activation in response to nuclear envelope defects could be to protect damaged cells against apoptosis (Wang et al 1999;Salminen et al 2011). Since a proper clearance of senescent cells by the immune system seems to be crucial for homeostasis maintenance in aging and cancer (Baker et al 2011;Kang et al 2011), both NF-kB hyperactivation and the subsequent age-related immunological decline could be compromising an appropriate response against age-accumulated senescent cells.…”
Section: G609g/g609gmentioning
confidence: 99%
“…The mechanism by which NF-kB signaling is activated with age also remains largely unexplored, but our data indicate that the nuclear envelope abnormalities occurring in both normal and premature aging (Scaffidi and Misteli 2006) may contribute, at least in part, to the activation of this inflammatory pathway. The primary function of NF-kB activation in response to nuclear envelope defects could be to protect damaged cells against apoptosis (Wang et al 1999;Salminen et al 2011). Since a proper clearance of senescent cells by the immune system seems to be crucial for homeostasis maintenance in aging and cancer (Baker et al 2011;Kang et al 2011), both NF-kB hyperactivation and the subsequent age-related immunological decline could be compromising an appropriate response against age-accumulated senescent cells.…”
Section: G609g/g609gmentioning
confidence: 99%
“…The increase of apoptosis resistance is a cell safety mechanism, because if cells have an acute stress due to some damage, they possess the capacity of recovering their homeostasis. However, in aging, when stress becomes persistent apoptosis resistance can cause the survival of undesired cells (Hampel et al, 2004;Salminen et al, 2011). It has been observed that the equilibrium between apoptotic and pro-apoptotic proteins changes with age.…”
Section: Changes In Gene Expression Growth Arrest and Apoptosis Resmentioning
confidence: 99%
“…Apoptosis markers such as FasL and cytochrome C decrease in serum and, on the other hand, levels of soluble Fas (an apoptosis inhibitor) increase (Kavathia et al, 2009). Salminen et al (2011) suggest that apoptosis resistance can affect the host's defenses in age-related fashion, a situation that meets promoted by the chronic inflammation that senescent cells develop.…”
Section: Changes In Gene Expression Growth Arrest and Apoptosis Resmentioning
confidence: 99%
“…3 The effect of PaM in improvement of oxidative stress following UVB and UVC irradiation has been established, 7 but did not for cellular apoptosis. Considering, severe oxidative stress is prerequisite for apoptosis triggered by UVB and posses an important role in aging process and frailty, 8,9 therefore, further research is needed to investigate the effect of PaM on antioxidant activity and hepatocyte cells apoptosis, and their relationship following UVB irradiation. Forty five percent of the total sunlight spectrum is UV light, consisting of UVA ranging from 315 -400 nm, UVB ranging from 280 -315 nm), and UVC ranging from 100 -280 nm.…”
Section: Introductionmentioning
confidence: 99%